Kajian Perempuan Pesisir dalam Mendukung Konservasi Sumberdaya Pesisir di Kabupaten Raja Ampat - Handayani Handayani; Endang Gunaisah (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2012)
The raja Ampat Regency is an archipelago area having petency of coanstal area resource which abundance,was but followed with the resource degradasi which caused for exampel by human being .Is so that needed strategy development of coastal are base on society .One of the social potency development is woman of coastal area. Research aim to analyse social factors woman of coastal arean and issues expanding in management of coastal area resource.obtained result that clan woman of dominant coastal area end comprehend informasi concering coastal area resource conservation besides clan woman of coastal area have readiness, caring and compleance to conservation which isn´t often him have interaction to in continuation of coastal area resource.